Analisis Kapasitas Lentur Balok Beton Bertulang Dengan Campuran Pasir Besi - Azwanda Azwanda; Chaira Chaira (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2020)
The use of concrete for structures in the field of civil engineering in particular, is currently increasing so as to demand better concrete technology. The purpose of this study was to analyze the flexural capacity of reinforced concrete beams with alternative materials using iron sand as a substitute for fine aggregate. In this study reinforced concrete beams with subtle aggregate substitution will be compared with normal reinforced concrete beams. The experimental method used to obtain data is carried out through flexural capacity testing. The results showed that the two beams failed to bend as planned. Normal flexural beam capacity is 10,480 tons with a maximum deflection of 7,530 mm. Whereas for flexible beams with fine aggregate substitution of iron sand obtained a deflection size of 18,470 mm with a maximum load of 11,860 tons. The crack pattern on the iron sand aggregate substitution beam has a higher amount where the crack appears slowly and has a shorter size compared to normal concrete blocks. Reinforced concrete beams with fine aggregate substitution of iron sand can also slow the initial cracking in normal reinforced concrete beams.